AN ANALYSIS OF MULTI-ETHNICS STUDENTS’ ATTITUDES IN THE TEACHING AND LEARNING OF HISTORY AT THE SELECTED SECONDARY SCHOOLS IN SABAH, MALAYSIA - Salleh, Mohamad Johdi; Agus, Ariegusrini (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
The purpose of this study is to examine the multi-ethnics students’ attitudes in the teaching and learning of History at the selected secondary schools in Sabah, Malaysia. This study was based on the data collected from questionnaires distributed to 189 students of various ethnicity including Dusun Bagahak, Suluk, Bajau, Chinese, Cocos, Iranun, Bugis, Kadazan, Timor, Tidong, Javanese, Orang Sungai, Kagayan, and, Malays. The data was analyzed by using convenience statistics such as frequency, mean, standard deviation, and, independent samples test. The results showed that the students’ interest, motivation, and, examination performance were greatly influenced by the teaching strategies of history teachers. The study suggests that if the teachers have the ability in attracting their students’ attention during the learning session, there will be great possibilities that the entire students regardless of gender and ethnics will love to learn History. It is hoped that more students would have benefits from this core subject of the lower and upper secondary levels, ICSS Malaysia, towards the realization of the first class human capital of Malaysian in the era of globalization.